Computerizing Values and Accessing Values via SMS - Imanuel Revelino Murmanto; Dina Fitria Murad (ULTIMA InfoSys, 2019)
The purpose of this study was to design an application to provide information to parents of SDK III BPK Penabur students regarding the exam schedule, and student grades via SMS. The design method used is the System Development Lifecycle method. The application design is done using the Visual Basic 6.0 programming language for designing application programs and interfaces and MySQL for designing the database. This application consists of several modules, namely the module processing data, processing values, processing SMS, and reports. The module is integrated to form a Computerized Value application and Value Access via SMS. In testing the application of Computerized Values ​​and Value Accessing Through SMS, white box testing and Black Box Testing methods are used. Tests are carried out at the module, program and system level. In addition, user testing is also done. The advantages of the application of Computerized Values ​​and Value of Access Through SMS help parents to obtain information about student learning outcomes, helping teachers to process student grades